Novel Insight into the Multiple Biological Characteristics of Polyamines in the Gut: From Structure to Function - Xinyi Yu; Shuzi Xin; Xiaohui Liu; Luming Pan; Weikai Shi; Yize Li; Hongli Wang; Xin Lu; Han Gao; Jingdong Xu (Frontiers in Bioscience-Landmark, 2025)
This review explores the structure of polyamines, including putrescine, spermidine, and spermine, and their crucial roles in immune cell functions. Polyamines are active compounds derived from ornithine that regulate signaling pathways by interacting with nucleic acids and proteins. Polyamines are essential for normal growth and development in immune cells, participating in cell signaling and neurotransmitter regulation and playing a critical role in immune responses. Notably, high concentrations of polyamines play a significant role in tumor cells and autoreactive B and T cells in autoimmune diseases. This impact should not be overlooked. Elevated levels of polyamines are associated with enhanced immune cell activity in tumor cells and autoimmune diseases. Furthermore, the connection between polyamines and normal immune cell functions, as well as their roles in autoimmune and antitumor immune cell functions, is significant. The role of polyamines in the normal function of activated T cells is well-established, and they are particularly important in antitumor immunity by modulating immune cell functions in the tumor microenvironment (TME). By synthesizing the latest research advancements, this review provides valuable insights into the roles of polyamines in immune regulation and outlines directions for future research.